2021
DOI: 10.3390/catal11060722
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chelating Agents to Enhance Fenton Process in Soil Remediation: A Review

Abstract: Persistent organic contaminants affecting soil and groundwater pose a significant threat to ecosystems and human health. Fenton oxidation is an efficient treatment for removing these pollutants in the aqueous phase at acidic pH. However, the in-situ application of this technology for soil remediation (where pHs around neutrality are required) presents important limitations, such as catalyst (iron) availability and oxidant (H2O2) stability. The addition of chelating agents (CAs), forming complexes with Fe and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 177 publications
(341 reference statements)
0
8
0
Order By: Relevance
“…The conventional Fenton process displays its maximum · OH production and subsequent pollutant oxidation activity in an acidic pH in the range of 2.8–3.5 30 , 31 . This pH medium, resulting in the use of strong sulphuric acid with ferrous and ferric catalysts and hydrogen peroxide, led to a degraded soil and microorganism community after treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional Fenton process displays its maximum · OH production and subsequent pollutant oxidation activity in an acidic pH in the range of 2.8–3.5 30 , 31 . This pH medium, resulting in the use of strong sulphuric acid with ferrous and ferric catalysts and hydrogen peroxide, led to a degraded soil and microorganism community after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…This again suggests that NA-COS and COS-Y chitin- and chitosan-oligosaccharides, respectively, might not work as effectively as expected for the elicitors for oxidative burst in vetivers. Therefore, further studies on the application of oxidative bursts and effective elicitors should be conducted 30 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it was not applied as a remediation process to degrade organics in aqueous solution until the late 1960s [15], and the use of this treatment for the removal of organics from soils was first evidenced in the 1990s [16]. However, at present it is the most common process for soil remediation [17].…”
Section: Fenton Processmentioning
confidence: 99%
“…Further clarification of the effects of radiation and the addition of pyridine on the LET will be performed in future work. Several prior studies 49,[57][58][59] demonstrated that the use of pyridine increases the rate of Fenton-like reactions via the formation of a complex. Consequently, we consider that the addition of pyridine does not affect the H 2 O 2 decomposition reaction with Fe 3+ , meaning that the sensitizing effect of H 2 O 2 on the dosimeter reduces the effect of LET.…”
Section: Effect Of Dispersant On Fe 3+ -Dhr123 Nc-rfgmentioning
confidence: 99%